Design of buried charged networks in artificial proteins - Mona Baumgart (Nature Portfolio, 2021)
Buried charged networks in proteins are often important for their biological functionality and are believed to destabilise the protein fold. Here, the authors combine computational design, MD simulations, biophysical experiments, NMR and X-ray crystallography to design and characterise artificial 4α-helical proteins with buried charged elements. They analyse their conformational landscapes and observe that the ion-pairs are stabilised by amphiphilic residues that electrostatically shield the charged motif, which increases structural stability.